2001
DOI: 10.1063/1.1355002
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a stratified lanthanum silicate dielectric by reaction with Si(001)

Abstract: We have characterized the structure and electrical properties of lanthanum silicate layers formed on Si(001) by reaction of lanthanum oxide with the substrate. Postoxidation of the deposited films results in the formation of a stacked dielectric with a lanthanum silicate layer atop an interfacial layer of SiO2. This structure combines the interfacial properties of SiO2 with the large permittivity of lanthanum silicate. Although the resulting film has leakage properties far superior to an equivalent thickness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
115
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(130 citation statements)
references
References 7 publications
12
115
3
Order By: Relevance
“…Since the dielectric constants ε of ionic conductors do not have much difference with each other, e.g. both the ε of YSZ and LSO are about 30 at room temperature [20,21], so the higher relaxation frequency f should be relate to the higher conductivity. This indicates that the composite materials have higher conductivity comparing to the single phase YSZ.…”
Section: Discussionmentioning
confidence: 99%
“…Since the dielectric constants ε of ionic conductors do not have much difference with each other, e.g. both the ε of YSZ and LSO are about 30 at room temperature [20,21], so the higher relaxation frequency f should be relate to the higher conductivity. This indicates that the composite materials have higher conductivity comparing to the single phase YSZ.…”
Section: Discussionmentioning
confidence: 99%
“…1,5,9 Upon diffusion, the aluminum and rare earth metals were found to react with the gate dielectric and interfacial SiO 2 layers. Some studies suggested the formation of silicates such as LaSiO x at the interface near the substrate, 14 while others indicated the formation of a HfLaSiO gate dielectric as a result of these reactions.…”
Section: à3mentioning
confidence: 99%
“…15 Regardless of the employed growth technique, LaSiO formation was indeed already reported either in as-deposited or in annealed La-based stacks. 63,64 Since the formation of such a LaSiO region can be mainly attributed to thermodynamical factors, it can be considered independent of the total film thickness. On the contrary, the total film thickness plays a fundamental role in establishing the electrical properties of the annealed layers.…”
Section: Si and Ge Diffusion: Formation Of Lasio And Lageo Speciesmentioning
confidence: 99%